2017
DOI: 10.1097/01.aog.0000513945.22985.af
|View full text |Cite
|
Sign up to set email alerts
|

Readability of Online Patient Educational Materials Provided by Major Gynecological Societies [16OP]

Abstract: INTRODUCTION: Major medical societies remain a reliable and accessible resource for online patient educational materials. While it is advised that patient educational materials remain at or below sixth grade reading level, the readability of most online educational content provided by such societies often exceeds this recommendation. Gynecological societies play an important role in providing online health information to women. However, a comprehensive review of non-obstetric patient education mate… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
5
0

Year Published

2018
2018
2021
2021

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(5 citation statements)
references
References 0 publications
0
5
0
Order By: Relevance
“…Individuals, especially younger adults, are increasingly connected to the digital world. In a 2016 survey, Americans expressed a preference for getting their news on a screen as opposed to a paper source, with only two in 10 U.S. adults get news from printed sources (Mitchell, Gottfried, Barthel, & Shearer, 2016). This is a decrease from earlier surveys and this decrease was most dramatic among persons aged 18 to 29 years (Mitchell et al, 2016).…”
Section: Introductionmentioning
confidence: 98%
See 4 more Smart Citations
“…Individuals, especially younger adults, are increasingly connected to the digital world. In a 2016 survey, Americans expressed a preference for getting their news on a screen as opposed to a paper source, with only two in 10 U.S. adults get news from printed sources (Mitchell, Gottfried, Barthel, & Shearer, 2016). This is a decrease from earlier surveys and this decrease was most dramatic among persons aged 18 to 29 years (Mitchell et al, 2016).…”
Section: Introductionmentioning
confidence: 98%
“…Eltorai, Ghanian, Adams, Born, and Daniels (2014) analyzed the reading level of accessible patient education materials on the American Association of Surgical Trauma website and found the average reading level was at a 10.9 grade level. Similarly, an analysis of educational materials for obstetrical/gynecological patients by Nwach et al (2017) found the average reading level to be at an 11.3-year grade level and that surgical related patient education materials were at a 13.5 grade level.…”
Section: Introductionmentioning
confidence: 99%
See 3 more Smart Citations